Criteria for the Nonexistence of Kneser Solutions of DDEs and Their Applications in Oscillation Theory - Osama Moaaz; Ioannis Dassios; Haifa Bin Jebreen; Ali Muhib (Applied Sciences, 2021)
The objective of this study was to improve existing oscillation criteria for delay differential equations (DDEs) of the fourth order by establishing new criteria for the nonexistence of so-called Kneser solutions. The new criteria are characterized by taking into account the effect of delay argument. All previous relevant results have neglected the effect of the delay argument, so our results substantially improve the well-known results reported in the literature. The effectiveness of our new criteria is illustrated via an example.